Stunting Prevention Strategy Through Increasing Community Participation Based on Gender Mainstreaming - Antonia Sasap Abao; Zakiah Hasan Gaffar; Annisa Rizqa Alamri; Agus Yuliono (Alfuad: Jurnal Sosial Keagamaan, 2024)
This article, "Strategy for Stunting Prevention Through Increasing Community Participation" is based on the "Gender Mainstreaming" Study in Kaliau Village, Sajingan Besar district, Sambas regency. The research uses a qualitative descriptive approach. Our findings indicate that the causes of stunting in children in Kaliau village are inadequate nutrition, low-quality sanitation, poor reproductive health conditions, and decision-making skills, limited health service facilities, relatively low education level of both mothers and fathers and subsequent poor parenting skills. The form of participation carried out by the community is generally vertical in nature, where most child-caring and rearing responsibilities are shouldered by mothers, and fathers' involvement is still very low. We suggest the need to improve educational activities for community health and sanitation, parenting skills, nutritional education on healthy eating patterns for infants, pregnant women, and nursing mothers, and to increase the involvement of men as fathers and posyandu cadres. Furthermore, we need to provide adequate health-service facilities and infrastructure for every community, vitalize the Youth Family Development program (B.K.R.), and improve the coordination among local stakeholders in the area. Lastly, adequate remuneration should be provided for posyandu cadres to help them work more effectively.